Implementation of Audiovisual Media in Improving Indonesian Learning Results About Writing Skills in SD Negeri 2 Penolih - A.R. Wulandari (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to improve the learning outcomes of students in the Indonesian Language Muple Writing Skills in Elementary School Class III with the learning model of Discovery Learning assisted by audiovisual media. The research conducted was a Classroom Action Research (CAR) in two cycles, with each cycle consisting of one meetings. The stages of each cycle are planning, implementing, observing and reflecting. Each meeting is carried out a pre test and post test to determine the progress of students. In the first cycle the students who completed after carrying out the post test were 58%. In the second cycle students who completed after carrying out the post test were 75%. These results indicate that the application of audiovisual media can improve student learning outcomes, especially Indonesian language muple in elementary schools